Fighting employment informality with schooling - Rodrigo R. Soares; Daniel Haanwinckel (IZA World of Labor, 2017)
Developing countries have long been struggling to fight informality, focusing on instruments such as labor legislation enforcement, temporary contracts, and changes in taxes imposed on small firms. However, improvements in the labor force's schooling and skill level may be more effective in reducing informality in the long term. Higher-skilled workers are typically employed by larger firms that use more capital, and that are more likely to be formal. Additionally, when skilled and unskilled workers are complementary in production, unskilled workers' wages tend to increase, adding yet another force toward reducing informality.
Keywords: J24; J31; J46; J64; O17; 330; informality; labor market; education; minimum wage; Brazil